Research hotspots and trends of immunotherapy and melanoma: A bibliometric analysis during 2014–2024 - Zixuan Jia; Youao Zhang; Luyan Cao; Jieyan Wang; Hui Liang (Human Vaccines & Immunotherapeutics)
Over the last decade, the increasing global prevalence of melanoma has sparked growing interest in immunotherapies, which show significant potential against this form of skin cancer. This research aims to offer a framework to guide future studies and inspire new research directions. In this study, we used the Web of Science Core Collection to collect papers on immunotherapy and melanoma published between 2014 and 2024. With Excel and visualization tools like VOSviewer, COOC 13.2, Citespace, and Bibliometrix (R-Tool of R-Studio), we analyzed the data to spot trends and new focuses in the research. Our findings indicate a substantial surge in research activity concerning immunotherapy and melanoma between 2014 and 2024. The USA and China emerged as leading contributors, engaging in extensive and close collaborative efforts with European counterparts. Furthermore, seven of the top 10 research institutions are located in the USA, with the MD Anderson Cancer Center in Texas being the most productive. In addition, the Journal of Cancer Immunotherapy is the journal with the most articles published in the field. Professor Georgina V. Long from the Melanoma Institute at the University of Sydney was one of the most productive scholars. Keyword analysis shows that immune checkpoint inhibitors, tumor microenvironment and targeted therapies are key areas of interest for the research community. This paper uses bibliometric analysis to outline research trends and key points in immunotherapy and melanoma from 2014 to 2024, which helps understand the current research and guides future research directions.